Effect of cryogenic cooling on the micro structure and properties of ferritic stainless steel welds - Mridha, Shahjahan (s.n, 2012)
In the present research, cryogenic cooling was applied in refining the weld microstructure and the dimension. The investigation was conducted by producing weld melts on a 1.5 mm thick FSS plate using TIG torch with different energy inputs in a pure argon environment. A Box- Behnken experimental design was adopted with current, traversing speed and the flow rates of cryogenic liquid as the process parameters. The weld microstructure was characterized using optical microscopy, X-ray diffraction, mechanical testing and fractography. The degree of grain refinement achieved was estimated using an innovative index known as Grain Refinement Index (GRI). This new scheme of cryogenic cooling created very significant level of grain refining of the weld structure and also reduced the weld geometry substantially. The heat affected zone (HAZ) is reduced by about 35% to that of the conventional weld; the grain size refined to a level where the weld joint ductility is 80% of the base metal without the formation of any brittle phase.